Reconstructing the biography of a Black Rail-mason: Isidro Allen Nava - Castillo Rodriguez, Jorge (2025)
This article presents the findings in the research for a project focused on the life of Isidro Allen Nava, a Mexican locomotive engineer of Afro-Jamaican descent who lived in San Luis Potosi in the early 20th century. The study is structured around three main axes of analysis: Allen Nava ethnicity´s, his connection to the railway industry, and his masonic career within the Lodge “Ignacio Ramírez” No. 10. The primary aim of this work is to shed light, through Allen Navas biography, on the close ties between the railway system and freemasonry.